Common beans, biodiversity, and multiple stresses: challenges of drought resistance in tropical soils - Beebe, Stephen E.; Rao, Idupulapati M.; Jyostna Devi, Mura; Polanía Perdomo, José A. (Commonwealth Scientific and Industrial Research Organisation, 2014)
Common bean (Phaseolus vulgaris L.) is the grain legume with the highest volume of direct human consumption in the world, and is the most important legume throughout Eastern and Southern Africa, cultivated over an area of ~4 million ha. In Sub-Saharan Africa (SSA) drought is the most important production risk, potentially affecting as much as one-third of the production area. Both terminal and intermittent drought prevail in different production regions. The Pan-African Bean Research Alliance (PABRA), coordinated by the International Center for Tropical Agriculture (CIAT by its Spanish acronym), has participated in projects for both strategic and applied research to address drought limitations, with research sites in six SSA countries. Bean originated in the mid-altitude neo-tropics, and by its nature is not well adapted to warm, dry climates. Efforts at genetic improvement of drought resistance have a long history, exploiting variability among races of common bean, as well as through interspecific crosses. Useful traits are found both in roots and in shoots. Many authors have stressed the importance of harvest index and related parameters to sustain yield of common bean under drought stress, and our field studies substantiate this. Additionally, in tropical environments, soil-related constraints can seriously limit the potential expression of drought resistance, and it is especially important to address multiple stress factors to confront drought effectively in farmers’ fields. Poor soil fertility is widespread in the tropics and constrains root and shoot growth, thus limiting access to soil moisture. Phosphorus and nitrogen deficiencies are especially common, but are not the only limiting soil factors. Soil acidity and accompanying aluminium toxicity limit root development and inhibit access to moisture in lower soil strata. Soil physical structure can also limit root development in some soils, as can poor soil management that leads to compaction. We review efforts to address each of these constraints through genetic means in combination with drought resistance per se.